An accurate spinal cord partition and quantification method to monitor atrophy in multiple sclerosis - Sahnoun, Mouna; Kallel, Fathi; Dammak, Mariem; Mhiri, Chokri; Ben Mahfoudh, Kheireddine; Ben Hamida, Ahmed (Signal, image and video processing, 2023)
MRI of the spinal cord (SC) has tremendous potential for improving diagnosis in multiple sclerosis (MS). In this paper, an accurate SC partition (SCP) and quantification method is developed allowing the study of SC atrophy in MS patient. The SC T2-w MR images for 70 subjects were investigated. After selecting the best region and slice, an intensity profile along polynomial SC centerline was generated allowing a precise intervertebral disk’s location. Disk’s widgets divide the SC into segments at every vertebra level. The volumes of SC segments were computed to estimate SC atrophy for MS patients. Results showed that the proposed algorithm was able to successfully partition and quantify SC segments in T2-w SC images. The robustness of the proposed method was evaluated for different SC curvatures and for different MR acquisition parameters. To evaluate the performance of our proposed SCP method, similarity and dissimilarity measures were calculated between the resulting SCP and the expert’ manual SCP. The resulting SC measures are justified favorably with the SC human anatomy. Results are compared to those obtained with healthy controls, presenting the highest Cervical SC (CSC) volume compared to SPMS (Secondary Progressive MS) and RRMS (Relapsing Remitting MS) patients. Proposed SCP method is prevalent to precisely partition and quantify SC and calculate its atrophy in case of MS neurodegenerative disease.